EVALUATION OF EFFECT OF REUSED EDIBLE OILS ON VITAL ORGANS OF WISTAR RATS - S., Shastry C.; Ambalal, Patel Narendrakumar; Himanshu, Joshi; J., Aswathanarayana B. (Journal of Health and Allied Sciences NU, 2011)
Objective: Cooking oils (edible oils) are vegetable oils which are extensively used for cooking in India. These edible oils are rich in triglycerides, sterol, tocoferol, carotenes and pigments. Upon frying, edible oils gives rise to formation of free radicals and other harmful agents. The degraded products of oils generated while cooking produce unfavorable effects. The present study was designed to evaluate the effects of reused edible oils (sunflower oil and palm oil) on vital organs of experimental animals.Materials and Methods: Wistar rats were fed fresh and reused edible oils - sunflower oil and palm oil (15 gm oil/100gm of feed consumed) and control group received normal food and water for a period of 8 weeks. The parameters studied include changes in physicochemical properties of reused oils, change in body weight of animals, plasma lipid profile, biochemical parameters and histopathological examination.Results: The result showed the change in physicochemical characteristics of reused oils. The animals fed with fresh and reused palm oil significant increase the body weight while reused sunflower oil fed group showed decrease significantly. The biochemical parameters, SGPT (serum glutamate–pyruvate transaminase), SGOT (serum glutamate- oxaloacetate transaminase), and ALP (alkaline phoshphatase) were increased in reused oils fed groups. The histopathological study showed the change in size of liver, heart, kidney and testes cells in reused oil groups.Conclusions: From the present study, it can be concluded that reused sunflower oil and palm oil, can be toxic and can cause considerable damage to the vital organs of the experimental animals.
Keywords: Edible oils; sunflower oil; palm oil; free radicals